H41 Working together to promote physical activity in people with huntington's disease. (September 2018) - Jones, Una; Hamana, Katy; Busse, Monica
Abstract : Background: Exercise for people with Huntington's disease (HD) is safe, feasible and has benefit for those taking part in the studies (Busse et al 2013, Quinn et al 2016), yet people with HD tell us they struggle to keep physically active. Aim: The aim of the study was to develop a tool to prompt discussion and identify physical activity goals to support people with HD become or stay physically active. Methods: People with HD (n=8), their family (n=10), healthcare professionals (n=6) and specialist HD advisors (n=4) attended an event in the United Kingdom. Attendees worked together to 'co-produce' a compilation of activities suitable for people with HD; applied this information to complete a prototype physical activity tool and provided feedback on the tool. This information was used to develop a more detailed physical activity tool that was presented to and reviewed at a Huntington's Disease Association family day attended by 104 members of the HD community. Result: A physical activity tool, PAT-HD, was developed based on existing research and feedback from people with HD, their carers, healthcare professionals and specialist HD advisors. The tool, an A4 double sided leaflet, consists of lists of activities suitable for people with HD and questions to facilitate discussion and personal goal setting for physical activity. People with HD felt that this was a useful tool that could be used in an easily accessible setting. Conclusion: The successful co-production of a physical activity tool for people with HD needs to be evaluated within a suitable setting.